Replication kinetics and infectivity of SARS-CoV-2 variants of concern in common cell culture models - Lena Mautner; Mona Hoyos; Alexandra Dangel; Carola Berger; Anja Ehrhardt; Armin Baiker (Virology Journal, 2022)
Abstract Background During the ongoing Covid-19 pandemic caused by the emerging virus SARS-CoV-2, research in the field of coronaviruses has expanded tremendously. The genome of SARS-CoV-2 has rapidly acquired numerous mutations, giving rise to several Variants of Concern (VOCs) with altered epidemiological, immunological, and pathogenic properties. Methods As cell culture models are important tools to study viruses, we investigated replication kinetics and infectivity of SARS-CoV-2 in the African Green Monkey-derived Vero E6 kidney cell line and the two human cell lines Caco-2, a colon epithelial carcinoma cell line, and the airway epithelial carcinoma cell line Calu-3. We assessed viral RNA copy numbers and infectivity of viral particles in cell culture supernatants at different time points ranging from 2 to 96 h post-infection. Results We here describe a systematic comparison of growth kinetics of the five SARS-CoV-2 VOCs Alpha/B.1.1.7, Beta/B.1.351, Gamma/P.1, Delta/B.1.617.2, and Omicron/B.1.1.529 and a non-VOC/B.1.1 strain on three different cell lines to provide profound information on the differential behaviour of VOCs in different cell lines for researchers worldwide. We show distinct differences in viral replication kinetics of the SARS-CoV-2 non-VOC and five VOCs on the three cell culture models Vero E6, Caco-2, and Calu-3. Conclusion This is the first systematic comparison of all SARS-CoV-2 VOCs on three different cell culture models. This data provides support for researchers worldwide in their experimental design for work on SARS-CoV-2. It is recommended to perform virus isolation and propagation on Vero E6 while infection studies or drug screening and antibody-based assays should rather be conducted on the human cell lines Caco-2 and Calu-3.